Celebrating women entrepreneurs through vendor business schools - Britanico, Stella Concepcion R.; Ricarte, Phoebe; Bertuso, Arma (CGIAR Initiative on Resilient Cities, 2024)
The VBS is a program of CGIAR Resilient Cities initiative that aims to empower small food vendors by providing them with vital knowledge, skills, and resources to overcome the challenges of their daily business operations and improve their food safety measures. Currently, the VBS program is being piloted in two countries, Philippines and Kenya. In the Philippines, CGIAR has partnered with the City Government of Quezon City to conduct the program from February to July 2024. Vendor participants are selected from private and public markets and temporary vending sites. The training and coaching sessions will cover topics on entrepreneurship, business planning, budgeting, marketing, risk management, adapting to technological changes, establishing financial connections, and ensuring food safety